Fate of trichothecene mycotoxins during the processing: milling and baking - Lancova, K; Hajslova, J; Kostelanska, M; Kohoutkova, J; Nedelnik, J; Moravcova, H; Vanova, M (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2008)
Toxic secondary metabolites produced by fungi representing Fusarium genus are common contaminants in cereals worldwide. To estimate the dietary intake of these trichothecene mycotoxins, information on their fate during cereal processing is needed. Up-to-date techniques such as high-performance liquid chromatography (HPLC) coupled with tandem mass spectrometry (LC-MS/MS) was used for the analysis of seven trichothecenes (deoxynivalenol, nivalenol, HT-2 toxin, T-2 toxin, 15- and 3-acetyldeoxynivalenol, and fusarenon-X) in bread production chain (wheat grains, intermediate products collected during milling and baking process, breads). Regardless of whether the grains were naturally infected or artificially inoculated by Fusarium spp. in the field, the fractions obtained from the grain-cleaning procedure contained the highest mycotoxin levels. During milling the highest concentrations of deoxynivalenol were found in the bran, the lowest in the reduction flours. Baking at 210 degrees C for 14 min had no significant effect on deoxynivalenol levels. The rheological properties of dough measured by fermentograph, maturograph, oven rise recorder, and laboratory baking test were carried out, and based on the obtained results the influence of mycotoxin content on rheological behaviour was investigated.
Keywords: jedlá semena; chromatografie kapalinová; Mass Spectrometry; Bread; manipulace s potravinami; trichotheceny; Flour; hmotnostní spektrometrie; Food Handling; Fusarium; Edible Grain; Trichothecenes; Chromatography, Liquid; mouka; chléb